Storytime Librarians Are Striving to Deliver Effective Storytime Programming to Children with Disabilities and Developmental Delays / Daskalakes, D. T. M., & Cahill, M. (2023). “We’re all pretty welcoming”: Inclusion of children with disabilities in library storytime programs. Journal of Early Intervention. Advance online publication. https://doi.org/10.1177/10538151231176193 - Phinney, Jackie (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2024)
Objective – To identify and characterize public librarians’ inclusion of children with disabilities and developmental delays (and their caregivers) in storytime programming, and to characterize how librarians determine if inclusion was successful.Design – Qualitative study using semi-structured interviews.Setting – Public library settings across Kentucky, Ohio, and Indiana (United States).Subjects – 34 public librarians offering storytime programming.Methods – The researchers invited all public libraries in the geographic area of interest to complete an internet survey expressing their interest in participating, and from the responses a stratified random sample of libraries was chosen. From each of these libraries, researchers randomly selected one storytime librarian to participate in the study. An experienced research team member conducted interviews using video conferencing software, and the other team member reviewed all transcripts to ensure accuracy. The researchers first analyzed the data using an inductive approach to generate descriptive codes. They then assigned these codes to the data that matched the study’s research questions. Finally, they conducted a third round of coding to describe some topics in greater detail.Main Results – Librarians are making attempts to be inclusive, and their attitudes toward children with disabilities and developmental delays (and their caregivers) are welcoming and flexible. However, they expressed limited experience in offering accommodations, and they perceived their positive attitude as being an accommodation in and of itself. Librarians are largely relying on the child’s experience to gauge how successful they are at being inclusive, and engaging in collaborative conversations with caregivers is also common.Conclusion – Overall, librarians are interested in offering programs that are accessible to children with disabilities and developmental delays but struggle to engage with meaningful accommodations that promote better educational outcomes. The authors emphasize that it is important for libraries to be welcoming of everyone, but more should be done to actually meet the needs of these patrons. This study has implications for public libraries and librarians, who should review their practices to ensure they are addressing the needs of children with disabilities and developmental delays and their caregivers. It also has implications for the profession, as it supports the idea that librarians should be better prepared to support these patrons in storytime programming and that institutions should facilitate librarian efforts through information exchanges. Finally, this study establishes that there is a need for further exploration of inclusivity for children with disabilities and developmental delays in storytime programming.